Relevance of Imidazoline Receptors and Agmatine to Psychiatry: A Decade of Progress - HALARIS, A; PILETZ, J E. (Annals of the New York Academy of Sciences, 2003)
: The cardiovascular relevance of imidazoline receptors (IR) has received tremendous attention since their discovery in 1984. However, evidence also has accumulated for the relevance of IR and an endogenous ligand, agmatine, to psychiatric disease. Emphasis has been placed on altered levels of the I1‐imidazoline site on human platelets and in human postmortem brain tissue from depressed patients. Attempts at exploring the molecular nature of the I1 protein have led to the cloning of a protein, IRAS. Based on transfection studies, IRAS seems to be involved in neuronal plasticity events. The I2 site also appears linked to psychiatric research since some of these sites are localized to a specific domain on monoamine oxidases. Different peptides have been identified by means of an imidazoline‐receptor‐binding‐protein (IRBP) antiserum, and these peptides, some of which appear to be fragments derived from IRAS, undergo changes in platelets and brain commensurate with altered mood states of the subject, notably depressive symptomatology. The search for an endogenous ligand for imidazoline receptor(s) also has led to agmatine, a decarboxylated derivative of arginine. Research on agmatine has mushroomed over the past several years and its measurement in the blood and brain has opened new research opportunities. This novel neurotransmitter interacts with a variety of receptors and has been implicated in mediation of stress responses, analgesia, drug addiction and withdrawal, convulsions, and neuroprotection. Given that IR and agmatine appear involved in a multitude of neurophysiologic and pathologic functions, the potential for new drug development is intriguing.